OPTIMASI PENEMPATAN DISTRIBUTED GENERATOR TERHADAP PERBAIKAN PROFILE TEGANGAN PADA PENYULANG ABANG MENGGUNAKAN METODE QUANTUM GENETIC ALGORITHM (QGA) - Dewa Gede Satria Bayu Putra; Antonius Ibi Weking; Widyadi Setiawan (Jurnal SPEKTRUM, 2018)
This research aims to optimize the Distributed Generator (DG) placement to improve the voltage magnitude on the Abang Feeder. The percentage of voltage drop received at the end of the load according to PLN is a maximum of 10% below the nominal voltage of a feeder. This study uses the MATLAB application with the Quantum Genetic Algorithm (QGA) method. The QGA method is an evolution of the Genetic Algorithm method which is combined with quantum calculations. This QGA method is combined with Newton Raphson's theory. The results obtained from this study are the placement of DGs in several buses on the broiler feeder and the improvement of the voltage magnitude that was previously not in accordance with standards ( below 18 kV or 0,9 p.u ) to be better ( 20 kV or 1 p.u and not more than 21 kV or 1,05 p.u ) and has met the predetermined standards.